miR-34 – a microRNA replacement therapy is headed to the clinic - Bader, Andreas G. (Frontiers in Genetics, 2012)
MicroRNA-34 is a master regulator of tumor suppression. It is downregulated in numerous cancers and inhibits malignant growth by repressing genes involved in various oncogenic signaling pathways. Consequently, miR-34 antagonizes processes that are necessary for basic cancer cell viability as well as cancer stemness, metastasis and chemoresistance. This broad anti-oncogenic activity holds the prospect of creating a new remedy that is effective against tumor heterogeneity. This review focuses on the molecular mechanisms of miR-34-mediated tumor suppression, pharmacologies in animal models of cancer and a status update of a miR-34 therapy that may be among the first miRNA mimics to reach the clinic.